Vsevolod Meyerhold - Pitches, Jonathan (London : Routledge, 2003)
Biography and context - Key writings - Key performances - Practical exercises
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Meyerhold, Vsevolod